2004
DOI: 10.1021/je049753h
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Phase Behavior of Systems with Ionic Liquids:  Part V. The Binary System Carbon Dioxide + 1-Butyl-3-methylimidazolium Tetrafluoroborate

Abstract: The phase behavior of the binary system consisting of the supercritical fluid carbon dioxide (CO2) and the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4]) was studied experimentally. A synthetic method was used to measure its phase behavior. Bubble-point pressures of the system CO2 + [bmim][BF4] are reported for carbon dioxide concentrations ranging from (10.22 to 60.17) mole % and within a temperature range of (278.47 to 368.22) K. The CO2 + [bmim][BF4] binary system has a two-phase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
110
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 35 publications
17
110
1
Order By: Relevance
“…The experimental data were taken from the literature Ren et al, 2010;Nwosu et al, 2009;Carvalho et al, 2009aCarvalho et al, , 2009bKroon et al, 2005;Liu et al, 2003;Ren and Scurto, 2009a;Shariati and Peters, 2003;Florusse et al, 2008) and the characteristics of these systems are shown in Table 2. The adjustable parameters, k ij and l ij , the %AARD and the range of experimental data utilized (expressed in pressure and liquid phase molar composition) are shown in Table 3 for all 17 binary systems analyzed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data were taken from the literature Ren et al, 2010;Nwosu et al, 2009;Carvalho et al, 2009aCarvalho et al, , 2009bKroon et al, 2005;Liu et al, 2003;Ren and Scurto, 2009a;Shariati and Peters, 2003;Florusse et al, 2008) and the characteristics of these systems are shown in Table 2. The adjustable parameters, k ij and l ij , the %AARD and the range of experimental data utilized (expressed in pressure and liquid phase molar composition) are shown in Table 3 for all 17 binary systems analyzed here.…”
Section: Resultsmentioning
confidence: 99%
“…Phase equilibria in systems composed of ionic liquids + CO 2 were studied by several authors Ren et al, 2010;Nwosu et al, 2009;Carvalho et al, 2009aCarvalho et al, , 2009bKroon et al, 2005;Liu et al, 2003;Blanchard et al, 1999), but few of them have assessed the solubility in ionic liquids of other gases. The phase equilibria of different imidazolium ionic liquids with 1,1,1,2-tetrafluoroethane (R-134a) were studied by Scurto (2009a, 2009b); the authors emphasize the importance of understanding these systems for the separation of hydrofluorocarbon refrigerant gases and in other engineering applications.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…The solubility of carbon dioxide in a variety of ILs has been determined at low pressures [1][2][3][4][5][6][7][8][9][10] and high pressures (up to 73 MPa) [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the system (carbon dioxide + [C 1 C 2 Im][NTf 2 ]), also investigated in this work, was studied by several authors [7][8][9][10]14,17].…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to this unique character of the phase behavior, the system has potential applications for extraction or purification as a green solvent. The solubility of CO2 in various RTILs has been extensively studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and the structure of the binary mixture has been studied experimentally and theoretically. [18][19][20][21][22] On the other hand, reports on transport properties of these systems such as viscosity and diffusion are still limited in spite of their importance in designing chemical processes.…”
Section: Introductionmentioning
confidence: 99%